2007
DOI: 10.1111/j.1440-1673.2007.01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Elastofibroma dorsi: Typical radiological features

Abstract: Elastofibroma dorsi is a rare benign and slow-growing fibro-proliferative lesion. It has a characteristic location (periscapular region) and a specific imaging appearance (sonography, CT, MRI) allowing accurate prospective diagnosis. The recognition of this benign lesion avoids unnecessary biopsy and/or surgery. We report two cases of bilateral elastofibroma dorsi illustrating characteristic imaging features on ultrasound, CT and MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Typically, the pattern of alternative hyperechoic and hypoechoic lines parallel to the chest wall is seen. 18 CT shows a heterogeneous soft tissue mass, often similar to weakened margins similar to skeletal muscle. On MRI, the fat tissue shows higher signal characteristics compared to the mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the pattern of alternative hyperechoic and hypoechoic lines parallel to the chest wall is seen. 18 CT shows a heterogeneous soft tissue mass, often similar to weakened margins similar to skeletal muscle. On MRI, the fat tissue shows higher signal characteristics compared to the mass.…”
Section: Discussionmentioning
confidence: 99%
“…USG shows an abnormal mass in the subscapular region. Typically, the pattern of alternative hyperechoic and hypoechoic lines parallel to the chest wall is seen 18 . CT shows a heterogeneous soft tissue mass, often similar to weakened margins similar to skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…This concept has been reinforced by other studies, particularly when used to supplement CT and MRI. [30][31][32][33] Battaglia et al 34 studied 43 patients with proven elastofibroma using ultrasonography followed by CT and MRI. It was shown that, if a typical fasciculated pattern was evident on ultrasonography, elastofibroma could be diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Although four of our earlier patients had a CTguided biopsy, this is no longer our standard practice since current evidence suggests that the lesion can be confidently diagnosed by radiological investigation alone if typical clinical features are present. [30][31][32][33][34][35][36] No benefits in any form have been received or will be received from a commercial party related directly or indirectly to the subject of this article.…”
Section: Discussionmentioning
confidence: 99%
“…It is rather the collaboration between clinicians and radiologists that can suggest the preoperative suspicion of ED [21,22]. Several papers in the recent literature indicate that imaging studies should be enough if the lesion is unilateral or asymmetrical, painful, with hard consistency, and rapidly progressing in volume [23][24][25]. Development of a tumoral mass in that specific region can include a number of differential diagnosis such as: Hemangioma, neurofibroma, malignant histiocytoma, lipoma [7,26,27], and requires an MRI with gadolinium contrast, thus the malignant tumors can be differentiated [23][24][25].…”
Section: Discussionmentioning
confidence: 99%